2001
DOI: 10.1079/phn200056
|View full text |Cite
|
Sign up to set email alerts
|

Dietary beliefs in the Baltic republics

Abstract: Objectives: As beliefs and knowledge about the possible effects of foods on health can influence food behaviours, this study examined selected dietary beliefs in the Baltic countries and the association of beliefs related to salt intake and to types of fat with food behaviours. Design: A cross-sectional study. Setting: Data from three surveys conducted in Estonia, Latvia and Lithuania in the summer of 1997 were used to describe the prevalence of dietary beliefs in these countries and to investigate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 12 publications
3
15
0
8
Order By: Relevance
“…Our data showed that highly educated respondents used vegetable oil more frequently than the less educated in all countries. It should be noted that the same association was also found to be true in the Baltic Nutrition Survey 24 . Looking at the educational gradient associated with spreading butter on bread, our data indicate differences between the countries.…”
Section: Discussionsupporting
confidence: 69%
“…Our data showed that highly educated respondents used vegetable oil more frequently than the less educated in all countries. It should be noted that the same association was also found to be true in the Baltic Nutrition Survey 24 . Looking at the educational gradient associated with spreading butter on bread, our data indicate differences between the countries.…”
Section: Discussionsupporting
confidence: 69%
“…Indigenous cultural and historical backgrounds overarch food preferences and food preparation methods, and these factors influence eating behaviors (Bronner et al, 2001; Pomerleau et al, 2001; Lau et al, 1984). Assessment of dietary practices among African-Americans requires culturally-specific information, not typically found in existing standard FFQs.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally nutritional research in Lithuania, as in other countries, has focused primarily on single nutrients or single food item and different dietary components have been suggested as important modifiable risk factors for chronic disease (Pomerleau et al 2001; Luksiene et al 2002; Vaicaitiene et al 2003; Grabauskas et al 2004). In the past decade, nutrition epidemiology has experienced a shift in focus from investigations at the level of individual nutrients to investigation at the level of foods and dietary patterns (Hu 2002; Kant 2004; Nettleton et al 2008).…”
Section: Introductionmentioning
confidence: 99%